Randomization in clinical trials - Rosenberger, William (Henry Stewart Talks, 2007)
Randomization model for clinical trials and comparison to traditional sampling-based models, Examples of randomization procedures used in practice, Exploration of randomization as a basis for inference under the framework of the family of linear rank tests, Randomization for the practicing biostatistician
Archived at 2018/05/31